Multiple correspondence analysis for characterization of growers based on agricultural practices: tomato crop in Caçador, Brazil (Revista de Ciências Agroveterinárias, 2015)
The objective was to characterize tomato growers from the region of Caçador, Brazil, using multiple correspondence analysis. Thirty-four tomato growers from Caçador were interviewed randomly from January to May, 2009. The questionnaire was based on the 2008 season and was composed of closed and open questions. The tomato growers were categorized, according to the planted area, in small (smaller than 2 ha), medium (from 2 to 5 ha), and large (larger than 5 ha) areas. The planted area was considered as an objective variable and the other variables (questions referring to the productive activities) were considered as explanatory variables, which means, those that best characterize the tomato growers according to the planted area. The data obtained was submitted to multiple correspondence analysis. This analysis allowed the characterization of the tomato growers from Caçador. Small tomato growers are more associated with agricultural practices that are not suitable with a rational tomato production system and they should be better trained by the technicians involved in the implantation process of the tomato integrated production system.
Keywords: Solanum lycopersicum; integrated production; farmers; diagnostics; multivariate statistics analysis.